An In-Depth Investigation of Investor Decision-Making and Cryptocurrency Market Dynamics - Masruroh, Laeli; Octafian, Ray (Institute Of Advanced Knowledge and Science, 2025)
This study aims to analyze the factors influencing cryptocurrency investment decisions, identify effective risk management strategies, and investigate the impact of institutional investment on the cryptocurrency market. Using a qualitative approach with semi-structured interviews involving eight experienced crypto investors, the research found that psychological factors such as FOMO (Fear of Missing Out) and herd mentality significantly affect investment decisions, with 87.5% of participants exhibiting both biases. Although all participants (100%) were aware of the high risks of crypto investments, there was a clear gap between risk awareness and the implementation of adequate risk management strategies, with only 50% using stop-loss orders and 62.5% still relying on informal, intuition-based approaches. Portfolio diversification (87.5%) and dollar-cost averaging (75%) were the most commonly applied strategies. Institutional investor involvement has increased market legitimacy (100%) and stability (75%) but has also raised concerns about higher correlation with traditional financial markets (62.5%) and potential price manipulation (62.5%). This study identifies a significant educational gap, particularly in risk assessment and regulatory understanding, emphasizing the importance of financial education and technological literacy in the cryptocurrency investment environment.